137Cs distribution in the South Caspian region, transfer to biota and dose rate assessment. Issue 5 (8th April 2020) - Abbasi, Akbar
ABSTRACT: According to a comprehensive environmental radioactivity survey in the South Caspian region, 137 Cs distribution in water, sediment and soil were measured in the Anzali lagoon of the Caspian Sea, Iran. An HPGe gamma-spectrometry system was used to determine the levels of 137 Cs in the water, sediment and soil samples. The bioconcentration guide (BCG), sum ratio factor (SRF), external dose rate, internal dose rate and total dose rate in aquatic animals, riparian animals, terrestrial animals and terrestrial plants were performed using the RESRAD-BIOTA code computer. The BCG range in the water, sediment and soil media were 1.58 × 10 3 Bq m −3 (riparian animals) to 1.83 × 10 9 Bq m −3 (terrestrial plants), 1.16 × 10 6 Bq kg −1 (riparian animals) to 3.65 × 10 8 Bq kg −1 (terrestrial plants), 7.69 × 10 2 Bq kg −1 (terrestrial animals) to 3.65 × 10 8 Bq kg −1 (aquatic animals), respectively. Also, the SRF values in the water, sediment and soil media were smaller than the unit. The order of the highest total dose rate to the lowest in three media was the terrestrial animal, terrestrial plant, riparian animal and aquatic animal, respectively. As well as terrestrial animal received 89% of total dose rates due to soil, sediment and water media.